Foreword to the thematic issue on cities in global capitalism - Peter Kumer; Danijel Davidovič (Journal for Geography, 2023)
This thematic issue investigates the complex interactions between urban environments and global capitalism. It includes a range of case studies and theoretical analyses that delve into the effects of global economic forces on urban spaces. The papers explore various topics, such as the transformation of labor markets due to digital capitalism, the impact of economic activities on urban climate resilience, and the challenges of sustainable urban development. The issue highlights the necessity of interdisciplinary approaches to understand and address the dynamic relationship between urban geographies and global economic systems.